Pengaruh Lingkungan Kerja, Budaya Kerja Dan Motivasi Terhadap Kinerja Karyawan Di Dinas Arsip Dan Perpustakaan Daerah Kabupaten Brebes - Hargisati Gendis Budihani; Nur Khojin; Azizah Indriyani; Muhammad Syaifulloh (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
In this modern era, employees who have good performance are really needed. The existence of libraries cannot be separated from community life. Libraries are important to meet the knowledge needs of someone who is looking for various reading sources. The aim of this research is to determine the influence of the work environment, work culture and work motivation on employee performance at the Brebes Regency Archives and Library Service The population in this study were employees of the Regional Archives and Library Service of Brebes Regency with a total of 36 respondents. The analysis used was descriptive analysis, SPSS 22. The results of this study were that the work environment had a positive and significant effect on employee performance, namely sig 0.001 < 0.05 and tcount 3.673 > 2.036. Work culture does not have a positive and significant effect on employee performance, namely sig 0.174 > 0.05 and tcount 1.390 < 2.036. Motivation has a positive and significant effect on employee performance, namely sig 0.020 < 0.05 and tcount 2.454 > 2.036. Based on the results of the F test carried out, the sign value is known. 0.000 < 0.05 and Fcount value 24.199 > 2.90 so it can be concluded that the variables of work environment, work culture, motivation simultaneously influence employee performance.